Customer relationship management association on financial strategy logistic service / Muhamad Fairos Mohamad Shah and Samsudin Wahab - Mohamad Shah, Muhamad Fairos; Wahab, Samsudin (2019)
Every business faces a threat or challenge at any part of life cycle in the business. These threats can be external or internal. This shows the importance of a business plan, because most threats or challenges are to be anticipated and plans put in place to cushion what effect they might bring to the business. In personal relationship is characterized by the human touch. Customer have the opportunity to interact while they are making their purchase decision sales. On the other hand retentive relationship refer to a long term relationship between the company and the customer. The more repeated customers the more it is assured and benefit for industries itself. The objective of this study to investigate the relationship financial strategy between customer relationship and management performance. A total of 391 respondent that answered the questionnaires as well as structural equation modelling as a method for this study.This study found that there is a significant relationship between variable and further study is recommended to investigate other factors. Last but not least, the implication of this study is that there are a lot of strategies that can be used for a retentive relationship and by giving customers a discount, even if it is a small one, or some add-ons unexpectedly, this will make customers come back for more.